TyTAN: Tiny trust anchor for tiny devices - Brasser, Ferdinand; El Mahjoub, Brahim; Sadeghi, Ahmad-Reza; Wachsmann, Christian; Koeberl, Patrick (Proceedings - ACM IEEE Design Automation Conference, 2015)
Embedded systems are at the core of many security-sensitive and safety-critical applications, including automotive, industrial control systems, and critical infrastructures. Existing protection mechanisms against (software-based) malware are inflexible, too complex, expensive, or do not meet real-time requirements. We present TyTAN, which, to the best of our knowledge, is the first security architecture for embedded systems that provides (1) hardware-assisted strong isolation of dynamically configurable tasks and (2) real-time guarantees. We implemented TyTAN on the Intel ® Siskiyou Peak embedded platform and demonstrate its efficiency and effectiveness through extensive evaluation.